1947
DOI: 10.1128/jb.54.3.305-323.1947
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Impurities on the Chemotherapeutic Action of Crystalline Penicillin

Abstract: 100; on a CDr0 unitage basis, 290 to 100. The relative efficacy of the various penicillins was closely comparable with that previously reported by ourselves 1We are indebted to Dr. R. Pasteruack and Dr. E. V. Brown of the Department of Research Chemistry of Chas. Pfizer & Co. for the preparation of the crystalline or purified penicillins dihydro-F, G, and K used in this study and to Mr. E. J. Goett of the Department of Research and Development, Chas. Pfizer & Co., for preparation of the impure fractions. We ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1948
1948
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Laboratory experiments with animals, and clinical trials and evaluations have shown that the relative effectiveness of the different penicillins in vivo depends upon the rate of excretion, degree of protein-binding in the blood, the pathogen involved, and several other factors. In practice, benzyl penicillin (penicillin G) has been found to be the most generally useful (38,59,60,61,99,101,166).…”
Section: Some Important Characteristics Of the Penicillinsmentioning
confidence: 99%
See 1 more Smart Citation
“…Laboratory experiments with animals, and clinical trials and evaluations have shown that the relative effectiveness of the different penicillins in vivo depends upon the rate of excretion, degree of protein-binding in the blood, the pathogen involved, and several other factors. In practice, benzyl penicillin (penicillin G) has been found to be the most generally useful (38,59,60,61,99,101,166).…”
Section: Some Important Characteristics Of the Penicillinsmentioning
confidence: 99%
“…One current trend in research aims at identifying chemically the various substances that may be present in impure penicillins and which at proper concentrations may shorten the lag period, before the onset of logarithmic growth in cultures of bacteria. This work takes on added significance in view of the recently renewed interest in amorphous (impure) penicillin, some lots of which have been shown to contain a factor or factors that are themselves inactive but that are capable of increasing markedly the effectiveness of pure penicillin in vitro (57), and especially interesting, its therapeutic effectiveness in vivo (101,199). Some of these enhancing factors may prove to be subtances that affect the systems regulating the respiratory processes of the pathogen cells, so that the cells become more susceptible to the action of penicillin.…”
Section: Amorphous Vs Crystalline Penicillinmentioning
confidence: 99%
“…It is a well-recognized fact that early amorphous penicillin contained varying proportions of penicillins X, G, dihydro-F, F, and K. It is, furthermore, recognized that impure penicillin contains varying amounts of the degradation products of these penicillins. That impure penicillin possesses greater chemotherapeutic action than crystalline penicillin G against certain experimental infections has been discussed in detail elsewhere (Hobby et al, 1946(Hobby et al, , 1947. The present report is incomplete in that only a portion of the penicillin degradation products have been tested.…”
Section: Discussionmentioning
confidence: 83%
“…It was concluded that the purification methods then in use resulted either in the removal or destruction of unknown compounds whose actions potentiated that of penicillin. 21 It is possible that vivicillin which was an unpurified preparation retained some of these compounds which led to its efficacy. More recent studies have revealed that a class of polysaccharide known as β-glucans present in the cell wall of fungi offers protection against pathogenic bacteria.…”
Section: The Scientific Basis For the Efficacy Of Vivicillinmentioning
confidence: 99%